Romeo and Juliet - Shakespeare, William, 1564-1616; Edited with a Commentary by Spencer, T. J. B. (London Penguin Books, 2015)
The greatest love story in English, William Shakespeare's Romeo and Juliet is a play of star-crossed lovers who take a valiant stand against social convention, with tragic consequences. This Penguin Shakespeare edition is edited with notes by T.J.B. Spencer, and an introduction by Adrian Poole.
Keywords: Italy--Verona -- Juliet (Fictitious character) -- Romeo (Fictitious character)